If it's not what You are looking for type in the equation solver your own equation and let us solve it.
41=-6(-3a+2)+5(1+6a)
We move all terms to the left:
41-(-6(-3a+2)+5(1+6a))=0
We add all the numbers together, and all the variables
-(-6(-3a+2)+5(6a+1))+41=0
We calculate terms in parentheses: -(-6(-3a+2)+5(6a+1)), so:We get rid of parentheses
-6(-3a+2)+5(6a+1)
We multiply parentheses
18a+30a-12+5
We add all the numbers together, and all the variables
48a-7
Back to the equation:
-(48a-7)
-48a+7+41=0
We add all the numbers together, and all the variables
-48a+48=0
We move all terms containing a to the left, all other terms to the right
-48a=-48
a=-48/-48
a=1
| 7x−4+x=−1+13x+7 | | -105=7(1-2x) | | -6j=-4-10j | | 2(4-4x)=7x+14-2x | | s+16.5=19 | | 7f-4-2=6f+2 | | -3(-5-3x)=87 | | 8w=-10+9w | | x+10°+3x+2°+4x-24°+2x+2°=360° | | h+28=12 | | 2c-2=4c+8 | | 7+2h=3h | | X-0.8x=174 | | 8(6+8x)=-336 | | 16v=54+7v | | -15+6n-n=6n-8 | | n/9=25/n | | -7(-3x-1)=91 | | 3/4.b=-15 | | r+8=44 | | 7u−10=5u+8 | | 90=-5(4x-6) | | -4n=-3-3n | | 4x+2(x+2)=3(2x+4) | | 2{4p+1}=10 | | -8-2v=-v | | 6x-5(x+5)=5x-6(x-4) | | 9-5w=-3w-9 | | 0^2=x+4 | | 4{x+1}-7=6x-2{4+x} | | b+1/6=-1 | | 45/3x+25=28 |